Disruption of Adipokinetic Hormone Mediated Energy Homeostasis Has Subtle Effects on Physiology, Behavior and Lipid Status During Aging in Drosophila - Bednářová, Andrea; Tomčala, Aleš; Mochanová, Michaela; Kodrík, Dalibor; Krishnan, Natraj (Frontiers in physiology, 2018)
The impact of disruption of adipokinetic hormone (AKH) signaling was studied during aging in Drosophila in a sexually dimorphic manner. A mutant (Akh1) producing a non-functional AKH peptide was compared with isogenized wild-type controls (w1118), and Akh-rescue line where AKH was ectopically expressed in the mutant background (EE-Akh). Longevity, fecundity, and locomotor activity rhythms remained unaffected by lack of AKH signaling. While the strength of rhythms declined in general with age across all fly lines tested this was more so in case of Akh1 flies. Negative geotaxis was significantly impaired in Akh1 flies. Only young Akh1 flies of both sexes and old Akh1 females showed significantly higher body weight compared to age-matched iso-control flies (except in case of EE-Akh). Expression of genes involved in energy homeostasis and aging indicated that dTOR and Akt expression were elevated in Akh1 flies compared to other genotypes, whereas AMPK and dFoxO expression levels were significantly reduced. Multivariate analysis of the distribution of lipid species revealed a significant accumulation of specific diglyceride (DG) and triglyceride (TG) lipid species, irrespective of sex, attributable in part due to lack of AKH. Moreover, irrespective of lack of AKH, older flies of all genotypes accumulated TGs. Taken together, the results strongly suggest that disruption of AKH has very subtle effects on physiology, behavior and lipid status during aging.
Keywords: AKH signaling; lipid status; senescence; aging; adipokinetic hormone; energy homeostasis